2023
DOI: 10.1038/s41467-023-36398-z
|View full text |Cite
|
Sign up to set email alerts
|

CLIC and membrane wound repair pathways enable pandemic norovirus entry and infection

Abstract: Globally, most cases of gastroenteritis are caused by pandemic GII.4 human norovirus (HuNoV) strains with no approved therapies or vaccines available. The cellular pathways that these strains exploit for cell entry and internalization are unknown. Here, using nontransformed human jejunal enteroids (HIEs) that recapitulate the physiology of the gastrointestinal tract, we show that infectious GII.4 virions and virus-like particles are endocytosed using a unique combination of endosomal acidification-dependent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…3B) through an indirect mechanism not yet characterized. These results are consistent with previous studies that have shown effects of cholesterol on GII.3 as well as GII.4 replication (28,34). The average human bile pool only contains trace amounts of highly hydrophobic bile acids like TLCA due to their cytotoxicity at higher concentrations (36,50).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…3B) through an indirect mechanism not yet characterized. These results are consistent with previous studies that have shown effects of cholesterol on GII.3 as well as GII.4 replication (28,34). The average human bile pool only contains trace amounts of highly hydrophobic bile acids like TLCA due to their cytotoxicity at higher concentrations (36,50).…”
Section: Discussionsupporting
confidence: 93%
“…HuNoV (28,34,44,45). We found that addition of cholesterol largely increased VLP binding, but only in the presence of bile acids (Fig.…”
Section: Bile Acids Exert a Direct Effect On Hunov Vlp Binding To Cellsmentioning
confidence: 64%
See 2 more Smart Citations
“…Excessive plasma membrane damage or defective plasma membrane repair is involved in many pathological conditions including muscular dystrophy, ischemia-reperfusion, heart failure, chronic inflammation, and neurodegenerative diseases [3]. Pathogens including parasites, bacteria, and viruses use diverse strategies to perforate the host cell plasma membrane and exploit the host cell repair responses to successfully infect their host [4][5][6][7][8][9]. In particular, the bacterial pathogen Listeria monocytogenes uses as a major virulence factor the pore-forming toxin listeriolysin O (LLO).…”
Section: Introductionmentioning
confidence: 99%